Antibiotic Susceptibility of Staphylococcus sp. in Diabetic Ulcer Patients at Dr. Mohammad Hoesin General Hospital, Palembang - Imaulina Sri Chelsee; Rizki Andini Nawawi; Masayu Farah Diba (Fakultas Kedokteran Universitas Sriwijaya, 2023)
The high prevalence of diabetic ulcers and the resistance of Staphylococcus sp. to antibiotics can complicate the treatment of diabetic ulcer patients with Staphylococcus sp. This study aimed to determine the pattern of susceptibility of Staphylococcus sp. in patients with diabetic ulcer at Dr. Mohammad Hoesin General Hospital Palembang in January 2019-August 2022. This research was an observational descriptive study using total sampling conducted in September-November 2022 at Dr. Mohammad Hoesin General Hospital Palembang. Data was obtained from patient medical records and laboratory results of patients with diabetic ulcer disease infected with Staphylococcus sp. from January 2019 to August 2022. Prevalence of Staphylococcus sp. infection in diabetic ulcer patients was low (15 of 77 diabetic ulcer patients, 19.5%). There were 19 bacterial isolates from 15 diabetic ulcer patients. A total of 8 coagulase-negative Staphylococcus sp. (CoNS) and 11 coagulase-positive Staphylococcus sp. (CoPS) isolates were tested for their susceptibility to antibiotics. Both CoPS and CoNS bacteria in diabetic ulcer patients were most susceptible to linezolid (90.9% for CoPS and 100% for CoNS) and most resistant to benzylpenicillin (81.8% for CoPS and 87.5% for CoNS).